Public health rationale for reducing sugar: Strategies and challenges. Issue 3 (3rd September 2020) - Stanner, S. A.; Spiro, A.
Abstract: The continuing global increase in the prevalence of overweight and obesity, particularly amongst children, attracts widespread public and political attention. Obesity is a complex condition, with multi‐faceted determinants, and prevention strategies require consideration of dietary and lifestyle patterns alongside a range of environmental factors. Reduction in intake of sugar‐sweetened beverages and foods is advised around the world as part of healthier dietary patterns to help reduce energy intakes, obesity risk and obesity‐related disorders. Current intakes indicate that this is challenging and will likely require a concerted approach with a broad range of interventions including fiscal measures. In recent years, after some notable success with salt and trans fats, there has been considerable focus on food reformulation to support the reduction in population intakes of free sugars from manufactured foods, often without need for consumer behaviour change. In some products, particularly sugar‐sweetened beverages, reformulation is relatively easy and has been widely achieved, as the sweetness of sugars can be replaced with low‐calorie sweeteners. However, other products, in which sugar delivers a variety of functional properties, are more challenging to reformulate to maintain consumer acceptance and achieve a reduction in energy, alongside sugar, content. This paper will look at current definitions and recommendations for free (or added) sugars, as well as key dietary sources and trends in intakes, and explore various strategies to promote population reductions in intake of sugars for public health, including the opportunities and challenges presented by reformulation using low‐calorie sweeteners. Ultimately strategies to promote sugar reduction, including reformulation, should adopt a holistic approach that considers wider dietary recommendations.